PERLINDUNGAN HUKUM TERHADAP KONSUMEN PINJAMAN OLINE DALAM SISTEM HUKUM INDONESIA - Mabsuti Mabsuti; Robby Nurtresna (Gapenas Publisher, 2022)
The presence of online loans is the impact of increasingly rapid technological advances. Online loans are in great demand by the public because of the ease of obtaining fresh funds, without complicated administration and requirements. However, people do not realize that behind the ease of getting fresh funds, the impact and risks of online loans are quite disturbing, because consumers who are unable to pay will be billed by being terrorized and even intimidated. The occurrence of various collection cases that violate human rights is actually caused by consumers who are unable to repay loans, because the interest is too high and indeed they are unable to pay. The legal umbrella for borrowing and borrowing cases is still lacking, because it has not been able to protect consumers who are intimidated because they are unable to pay, and also because they cannot protect lenders who suffer losses due to default